2021
DOI: 10.1186/s13690-021-00702-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the COVID-19 related behaviors in the public transport system

Abstract: Background Determining people’s healthy behaviors related to COVID-19 could be effective in providing preventive measures. The present study aims to investigate preventive behaviors associated with COVID-19 including wearing masks and keeping physical distance among the passengers on buses and public taxis measures to evaluate the ventilation systems in these vehicles. Methods This cross-sectional study was performed on 753 passengers on buses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Aghdam et al [22] investigated COVID-19-related behaviors in the public transport system; their results suggest that gender, type of vehicle, age, and SES were significant predictors of nonadherence to COVID-19 preventive behaviors in public transport during the pandemic. Still, some authors have attempted to understand public transport satisfaction after the COVID-19 pandemic [23].…”
Section: Introductionmentioning
confidence: 99%
“…Aghdam et al [22] investigated COVID-19-related behaviors in the public transport system; their results suggest that gender, type of vehicle, age, and SES were significant predictors of nonadherence to COVID-19 preventive behaviors in public transport during the pandemic. Still, some authors have attempted to understand public transport satisfaction after the COVID-19 pandemic [23].…”
Section: Introductionmentioning
confidence: 99%
“…Such centers should be established in our country to increase children's access to booster seats and its application. Studies have shown the frequency of healthy behaviors in the environment causes more people to do them (12,32,(31)(32)(33)34).…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary because the use of face masks, enhanced cleaning and disinfection, and public awareness campaigns, are some of the measures considered effective in preventing the spread of COVID-19 on public transportation in China and allowing the country to gradually restore public transportation services (Shen et al, 2020). Studies have shown that mandatory mask policies are associated with a reduced risk of COVID-19 morbidity and reduce the risk of infection by 85% (Aghdam et al, 2021). The use of masks is effective because aerosols can collect and remain infectious in indoor air for hours (Prather et al, 2020).…”
Section: Mask-wearingmentioning
confidence: 99%
“…WHO recommends that individuals wash their hands regularly with soap and water or use an alcoholbased hand sanitizer (WHO, 2020). Research conducted by (Aghdam et al, 2021)on 365 passengers on the public transportation system in Iran during the COVID-19 pandemic, the results showed that the majority of public transportation passengers in Iran had complied with COVID-19-related behaviors such as wearing masks and maintaining physical distance from people. other.…”
Section: Hand Hygiene and Sanitizationmentioning
confidence: 99%